2016
DOI: 10.1039/c5ra19747c
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of monolayer MoS2, MoSe2, and WS2: interplay of mass effect, interatomic bonding and anharmonicity

Abstract: Phonons are essential for understanding the thermal properties in monolayer transition metal dichalcogenides, which limit their thermal performance for potential applications. We investigate the lattice dynamics and thermodynamic properties of MoS 2 , MoSe 2 , and WS 2 by first principles calculations. The obtained phonon frequencies and thermal conductivities agree well with the measurements. Our results show that the thermal conductivity of MoS 2 is highest among the three materials due to its much lower ave… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
189
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 306 publications
(219 citation statements)
references
References 63 publications
26
189
2
2
Order By: Relevance
“…The amount of strain is evaluated by carefully examining the photon energy in the PL spectra under similar excitation conditions, which is 0.6% for the WS 2 in MoS 2 :hBN:WS 2 VLHs and 0.12% for the MoS 2 in WS 2 :hBN:MoS 2 VLHs . The monolayer WS 2 is more strained than the MoS 2 due to the higher growth temperature of WS 2 and their similar calculated linear thermal expansion coefficients relative to the SiO 2 /Si substrate, while the cooling procedures in CVD and characterization parameters are kept identical. The presence of strain causes band gap modification, which will change the relative band offsets between WS 2 and MoS 2 monolayers and in turn the details of the type II heterostructure .…”
Section: Resultsmentioning
confidence: 99%
“…The amount of strain is evaluated by carefully examining the photon energy in the PL spectra under similar excitation conditions, which is 0.6% for the WS 2 in MoS 2 :hBN:WS 2 VLHs and 0.12% for the MoS 2 in WS 2 :hBN:MoS 2 VLHs . The monolayer WS 2 is more strained than the MoS 2 due to the higher growth temperature of WS 2 and their similar calculated linear thermal expansion coefficients relative to the SiO 2 /Si substrate, while the cooling procedures in CVD and characterization parameters are kept identical. The presence of strain causes band gap modification, which will change the relative band offsets between WS 2 and MoS 2 monolayers and in turn the details of the type II heterostructure .…”
Section: Resultsmentioning
confidence: 99%
“…Lahiri et al [56,57] confirmed this mechanism in aluminum matrix. In this study, thermal expansion coefficient for carbon nanotubes, tungsten sulfide and aluminum are equal to 2×10 −5 K −1 , 14.8×10 −6 K −1 , 24×10 −6 K −1 respectively [58,59]. There is a significant difference between the thermal expansion coefficient of the reinforcements and matrix, which causes the thermal stress in the reinforcement interface area in matrix and around the reinforcement themselves.…”
Section: The Main Affecting Factors On Strengthening Of Hybrid Nanocomentioning
confidence: 95%
“…The calculated Debye temperature for borophene is 863.86 K, which is higher than that of monolayer MoS 2 (262.3 K) 33 and black phosphorene (500 K) 53 , but lower than that of graphene (2,300 K) 54 . Concerning thermal vibrations, the Debye temperature is a measure of the temperature above which all modes begin to be excited 55 , which will further affect the heat transport in borophene.…”
Section: B Optical Properties Of Borophenementioning
confidence: 97%
“…The bond length of B 1 -B 1 and B 2 -B 2 bonds along the a direction is 1.613 Å, and that of B 1 -B 2 bonds is 1.879 Å. In contrast to 2D honeycomb materials [31][32][33][34] , borophene has a highly anisotropic crystal structure with space group Pmmn 9 .…”
Section: Methods and Computational Detailsmentioning
confidence: 99%